Organizational memory and its role for the knowledge management - Freire, Patrícia de Sá (2012)
DOI: http://dx.doi.org/10.5007/2175-8077.2012v14n33p41This study presents the conceptualization of organizational memory, its role in knowledge management and the importance of knowledge media for its construction. For this purpose, an exploratory research has been held on a theoretical basis. The results indicate that knowledge management is a supporting tool for knowledge creation and its maintenance within the organization, since it enables knowledge existing in people’s minds, and in the actions of their work practices, to be shared, recorded, preserved as an organizational memorial, and subsequently disseminated. The conclusion is that knowledge media, rather than simply disseminating organizational knowledge, have multiple roles in the permanent whole construction of knowledge. The media enable the creation of new contents, arouseinterest, attract attention, nurture socialization and record and disseminate knowledge, thus favoring its explicitness.